The mediating effect of self-efficacy on family functioning and psychological resilience in prostate cancer patients - Zhou, Yao; Shan, Honglan; Wu, Cuigan; Chen, Haiyan; Shen, Yuanyuan; Shi, Wenying; Wang, Lina; Li, Qinghe (Frontiers in Psychology, 2024)
Aims Prostate cancer patients face impaired body image and psychological distress during the diagnosis and treatment of the disease, which leads to changes in mood, cognition and behavior. Psychological resilience has been shown to buffer shocks and stresses from the disease. Therefore, this study investigates the relationship between family functioning and psychological resilience in prostate cancer patients and the mediating role of self-efficacy between family functioning and psychological resilience to provide a relevant theoretical basis for improving patients' psychological status by providing relevant theoretical basis. Method Using a cross-sectional design, participants were 215 patients with prostate cancer admitted to and treated in a tertiary hospital in Jiangsu province, China. Questionnaires were administered using the general information questionnaire, the Connor-Davidson Resilience Scale (CD-RISC), the Family Adaptation, Partnership, Growth, Affection, and Resolution Index (APGAR), and the General Self-efficacy Scale (GSES). Data were analyzed using descriptive and correlational analyses and the bootstrap mediation test was used to test the effect relationship between the variables. Results Family functioning, self-efficacy and psychological resilience were significantly and positively correlated (r = 0.526, P < 0.01; r = 0.378, P < 0.01; r = 0.358, P < 0.01). The mediating effect of psychological resilience between family functioning and psychological resilience was significant, accounting for 42.56%. Conclusion Family function and self-efficacy have been shown to increase the level of psychological resilience in prostate cancer patients. Attention should be paid to the mental health problems of prostate cancer patients, early screening and intervention, and the use of patients' family resources to improve their confidence in recovering from the disease, thus increasing their psychological resilience and improving their mental health.